Ghāyat al-Maqṣūd by Muḥaddis̲Shams al-Ḥaqq ʻaẓīm Ābādī: Analysis and Description - Dr. Yasir Farooq; Dr. Arshad Munir (jihat-ul-islam, 2023)
To preserve the hadiths of the Prophet (PBUH), scholars have served from many aspects and sources. The editing of hadith began in the era of the Prophet (PBUH) and flourished during the period of the Companions and followers and the period of moḥaddīthīns. Sunan Abu Dawood, whose author is Imam Abu Dawood AlSajistānī is well known book of ḥadīth. From early to late Muslim scholar paid utmost efforts on its commentaries both in Urdu and Arabic languages. Ghāyat al-Maqṣūd is one of the finest commentary of Sunan Abū Dawood, and only one volume of this literary commentary has been published by Ansari publishing house, Delhi. Moḥaddith Shams al-Ḥaq ʻAẓīm Ābādī consulted all existing classical and traditional literature of his time. Among his main sources were the books of hadith and sīrah, jurisprudence, history, and Arabic dictionaries. This paper deals with the key features and characteristics of Ghāyat al-Maqṣūd and its methodology.